PEMBUATAN MEDIA AJAR RANGKAIAN LISTRIK DAN SIMULASI MELALUI APLIKASI SIMURELAY - Afrizal, Ragil; Maulana, Irfan; Aswin, Fajar; Ramli, Ramli (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The problem in the practicum of electrical circuits at the Bangka Belitung State Manufacturing Polytechnic is the unavailability of structured, safe, and effective teaching media. This causes difficulties for students in understanding the concept of wiring diagrams, the use of electrical components, as well as motor control and lighting systems. The purpose of this final project is to design and create simulation-based teaching media for electrical circuits using the Simurelay application. The methods used include data collection through observation, interviews, and practical experience evaluation. The media is designed using industry standard electrical components such as contactors, relays, transformers, timers, and 3-phase electric motors. The test results showed that all circuits, including AC/DC light circuits, traffic light simulations, and CW, CCW, and star-delta motor controllers, were successfully executed according to function. Simulations using the Simurelay application confirm that the designed scheme has run well and according to plan. This media is considered to facilitate the learning process, improve understanding of basic electrical concepts, and support safety and efficiency in practicum. Thus, this teaching media is feasible to be applied as a teaching aid in the technical vocational education environment.